Isolasi dan Identifikasi Agrobacterium Tumefaciens pada Tanaman Mawar (Rosa sp.). - SILITONGA, NADIAH; WIRAWAN, I GEDE PUTU; SUSRAMA, I GEDE KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.3, No.3, Juli 2014, 2014)
ABSTRACT Isolation and Identification of Agrobacterium tumefaciens At Plant roses ( Rosa sp.). Agrobacterium tumefaciens caused crown gall tumor in many of dicotyledonous plants. The purpose of this study tried to isolate and identify the A. tumefaciens from rose plant. Various techniques were used such as selection media, colonies shape and color, Koch's postulate test, DNA isolation and agarose gel elektroforesis. The results of this study showed that A. tumefaciens can be isolated through culturing in LB medium and selection AB medium that was specific for A. tumefaciens . The isolate caused crown gall tumor on carrot slice 3 weeks after inoculation by using a modified Koch’s postulate test. The characteristics of colony formed in this research are round shaped, cream coloured with pink tint, smooth edge, and convex elevation. DNA isolation and its running in agarose gel electroforesis showed positive result.   Key words : Agrobacterium tumefaciens , AB medium and Agarose gel electroforesis.